Renesansowy poemat "Sarca" jako "aemulatio" z autorami antycznymi - Kowalczyk-Cantoro, Daria (Collectanea Philologica, 2021)
The aim of this article is to analyse the Renaissance poem Sarca, whose authorship is attributed to the Italian humanist Pietro Bembo, and to indicate the ancient inspirations of the work. The main model for the work is Carmen 64 by Catullus, although the author also refers to other Roman poets. The intertextual relations between Sarca and the hypotexts are presented on various levels. The analysis focuses on showing parallel elements of the setting and takes in consideration the few similarities at the linguistic and stylistic level. Genre-wise Sarca is classified as an epithalamium of an aythiological character. Its characteristics typical of the Renaissance era are also highlighted. The article also brings up the history of the poem and the topic of its attribution, presenting an extensive state of research.